Adaptation of the Ukraine educational space to the conditions of the information society - Sukhova, N.; Kadnikova, L. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2017)
The article is devoted to the problems of adaptation of the Ukrainian educational space to the conditions of the Euro-pean type Information society. The authors consider the impact of Ukrainian society negative phenomena upon the processes of reforming secondary and higher education.